2014
DOI: 10.2478/s13382-014-0306-4
|View full text |Cite
|
Sign up to set email alerts
|

Across-shift changes of exhaled nitric oxide and spirometric indices among cotton textile workers

Abstract: Objectives: For the purpose of evaluation of exhaled NO as an index of airway inflammation, we assessed changes in fractional exhaled NO (FeNO) across a work shift and its relationship with respiratory complaints. Material and Methods: Chronic and work-aggravated respiratory complaints were assessed using a questionnaire in 89 male textile workers. FeNO and spirometry were performed before and after a work shift and all the changes were registered. Results: A significant increase in FeNO after a work shift was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
2
4
1
1
Order By: Relevance
“…The overall prevalence of chronic respiratory symptoms in this study (54%) was comparable to previous research conducted in similar low-and middle-income settings such as in Ethiopia (48%) [30], Egypt (59%) [9], Nigeria (62%) [11], and Bangladesh (53%) [31]. However, the prevalence was higher than the study conducted in an Iranian textile factory (26%), where workers were relatively younger [16].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The overall prevalence of chronic respiratory symptoms in this study (54%) was comparable to previous research conducted in similar low-and middle-income settings such as in Ethiopia (48%) [30], Egypt (59%) [9], Nigeria (62%) [11], and Bangladesh (53%) [31]. However, the prevalence was higher than the study conducted in an Iranian textile factory (26%), where workers were relatively younger [16].…”
Section: Discussionsupporting
confidence: 73%
“…The highest average inhalable dust exposure level was recorded in the carding section in the spinning department [26]. In a similar study, a higher cross-shift reduction was reported in spinning [15,16]. However, in our study, a high prevalence of chronic respiratory symptoms, but with the lowest cross-shift reduction, was found in the finishing department.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…16,17 Elevated FeNO levels are associated with increased respiratory complaints in cotton mill workers. 18 Furthermore, increased respiratory symptoms and pulmonary function abnormalities are higher in cotton workers compared with matched controls. 19 Therefore, cotton dust plays an important role in initiation of respiratory health problems.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Some other factors such as BMI or some other occupational or environmental exposures may affect FeNO as well. [ 11 12 ]…”
Section: Introductionmentioning
confidence: 99%